2021
DOI: 10.1080/08856257.2021.1872999
|View full text |Cite
|
Sign up to set email alerts
|

Relational competence regarding students with ADHD – An intervention study with in-service teachers

Abstract: Research suggests that supportive teacher-student relationships are a prerequisite for student development. Developing such relationships requires teachers to observe, interpret, and reflect on teacher-student interactions and on teachers' relational competence in practice. Although teacher-student relationships are especially challenging with students with attention deficit hyperactivity disorder (ADHD), few studies have examined how these relationships develop. In this qualitative study, teachers from two Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Previous research (Ansari, Hofkens, and Pianta, 2020; Aspelin and Jonsson, 2019; Ewe and Aspelin, 2021) has shown that teachers' sensitivity to students' needs is directly related to students' academic and social success. Teacher‐student relationships are even more challenging for SECs (Ewe and Aspelin, 2021). Aspelin and Jonsson (2019) defined teachers' relational competence as teachers' sensitivity to the feelings of their students, their empathy and sense of openness, and respect for the students and their parents.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous research (Ansari, Hofkens, and Pianta, 2020; Aspelin and Jonsson, 2019; Ewe and Aspelin, 2021) has shown that teachers' sensitivity to students' needs is directly related to students' academic and social success. Teacher‐student relationships are even more challenging for SECs (Ewe and Aspelin, 2021). Aspelin and Jonsson (2019) defined teachers' relational competence as teachers' sensitivity to the feelings of their students, their empathy and sense of openness, and respect for the students and their parents.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Teacher-student relationships are even more challenging for SECs (Ewe and Aspelin, 2021). Aspelin and Jonsson (2019) defined teachers' relational competence as teachers' sensitivity to the feelings of their students, their empathy and sense of openness, and respect for the students and their parents.…”
Section: Attitudes Towards Students With Educational Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from another study with a similar purpose and design but a focus on experienced teachers (n 53) showed that the participants, with the support of the intervention, shifted from making assertions about relational qualities solely on the basis of the teachers' behavior to acknowledging the students' perspectives. The teachers also shifted from making unsupported claims about relationships to supporting their interpretations with behavioral markers, and from an everyday discourse on interpersonal relationships to a more precise relational discourse (Ewe and Aspelin, 2021).…”
Section: Previous Research Teachers' Relational Competencementioning
confidence: 99%
“…An interesting difference between the results of the present study and those of another Swedish study (Aspelin and Jonsson, 2019) is that the pre-service special educators in this study were already focusing on pedagogical practice in their first analysis, whereas the pre-service teachers in the other study focused on applying "external" and "internal" explanatory models, for example explained the activity in terms of curricula or the teacher's personal characteristics. Another Swedish study (Ewe and Aspelin, 2021) showed that inservice teachers had an initial focus similar to that of the preservice special educators. These findings indicate that experienced educators focus more on actual teaching processes, while pre-service teachers tend to seek more abstract explanations.…”
Section: Pre-service Special Educators' Relational Competencementioning
confidence: 99%